A history of the growth and development of the Seventh-Day Adventist Church in Southern Africa, 1920-1960 - Thompson, Ronald Charles Lloyd (Rhodes University, Faculty of Divinity, Department of Divinity, 1979)
From Introduction: The most natural divisions of time for this historical survey of the growth and development of the Seventh-day Adventist Church in Southern Africa fall into three periods: (1) from 1920, when the African Division of Seventh-day Adventists was organized, to 1931, when it was reorganized under the name Southern African Division; (2) from 1931 to 1945, covering the period years of the Great Depression and Second world War; (3) from 1946 to 1960, the post-war. Attention is given in Chapter I to a certain phase of church development because the church had emerged at the highest level of Adventist organization, i.e. a Division. Although the first group of Adventists adopted the simplest form of organization in 1892 known as the South African Conference, the church was small and little known. The church at Division level therefore embarked on a programme of orientation and adaptation to gain recognition and make itself known everywhere. Closely allied to this was organization. Chapter II defines the organization of the church and explains how it was financed. The history of its organization and reorganization is also traced. Chapters III and IV deal with an era of expansion during the twenties in the establishment of missions, medical missions and training institutions, while new mission fields were entered and old mission fields were further developed. Chapters V and VI continue to trace the development of missions, mission fields, medical missions, and training institutions together with important changes in the medical and educational work. Further reorganization and new developments in the European church and African church are also outlined. The great emphasis on expansion and the development of institutions finally reached a point whereby "institutionalism" overtook "evangelism". Chapter VII discusses this problem and what was done to try and arrest it. Thus the history of the church is brought to an interesting turning point and climax in Part Two. Chapter VIII breaks from the common run of growth and development in missions, medical missions and institutions and traces the development of the principles and practice of the Adventist Church. The Southern African Division set itself the objective of full maturity in the establishment of a self-supporting, self-governing and self- propagating church in Africa. The history of these principles are covered together with the principles governing the reception of government grants-in-aid. Chapter IX deals with the analysis and development of the three-fold ministry of teaching, preaching and healing. These chapters in Part Three do not constitute a conclusion but simply give further insights in the growth and development of the church .
Keywords: Seventh-Day Adventists -- South Africa -- History